Levan Nanostructured Thin Films by MAPLE Assembling - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP (AMER CHEMICAL SOC, 2011)
Synthesis of nanostructured thin films of pure and oxidized levan exopolysaccharide by matrix-assisted pulsed laser evaporation is reported. Solutions of pure exopolysaccharides in dimethyl sulfoxide were frozen in liquid nitrogen to obtain solid cryogenic pellets that have been used as targets in pulsed laser evaporation experiments with a KrF* excimer source. The expulsed material was collected and assembled onto glass slides and Si wafers. The contact angle studies evidenced a higher hydrophilic behavior in the case of oxidized levan structures because of the presence of acidic aldehyde hydrogen bonds of the coating formed after oxidation. The obtained films preserved the base material composition as confirmed by Fourier transform infrared spectroscopy. They were compact with high specific surface areas, as demonstrated by scanning electron and atomic force microscopy investigations. In vitro colorimetric assays revealed a high potential for cell proliferation for all coatings with certain predominance for oxidized levan.
Keywords: FREE-ENERGY ANALYSIS; EVAPORATION; LASER; IMMOBILIZATION; POLYMERS